The Need of Backpacking Tourists in Non-Star Hotels: Insights from Gorontalo City, Indonesia - Krishna Anugrah; Meilinda Lestari Modjo; Nur Anjeli (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2021)
Gorontalo is a transit city for foreign tourists that will continue their trip to Togean islands, or for tourists coming from Togean islands that will continue the trip to Manado, Makassar, or Jakarta. Foreign tourists who opt to transit in Gorontalo prefer non-star hotels as their accommodation option. This study aimed to analyze the guest’ needs from five kinds of dimension, i.e., tangible dimension, empathy dimension, reliability dimension, responsiveness dimension, and assurance Dimension. The present study integrated a qualitative and a simple quantitative method as the research design. The data were directly collected by field observation; questionnaires distributed to the tourists were employed to collect the main data, while the supporting data were extracted by interview and documentation. As based on the findings, the backpackers’ needs for basic tangible goods involve food three times a day, a heat pump water heater, and laundry service. In accommodating the needs, the hotels can cooperate with third parties, particularly regarding food three times a day and laundry service. Moreover, the intangible service-oriented needs comprise empathy, reliability, responsiveness, and assurance. As based on the questionnaire, the respondents showed good responses and suggested improvements in several aspects, particularly on the intangible needs.